Efficacy and survival in patients with cardiac contractility modulation: long-term single center experience in 81 patients - Kuschyk, Jürgen; Röger, Susanne; Schneider, Raphaela; Streitner, Florian; Stach-Jablonski, Ksenija; Rudic, Boris; Weiß, Christel; Schimpf, Rainer; Papavassiliu, Theano; Borggrefe, Martin (International journal of cardiology, 2015)
To analyze long-term efficacy and survival in patients with chronic heart failure treated with cardiac contractility modulation. 81 patients implanted with a CCM device between 2004 and 2012 were included in this retrospective analysis. Changes in NYHA class, ejection fraction (EF), Minnesota Living with Heart Failure Questionnaire, NT-proBNP and peak VO2 were analyzed during a mean follow up of 34.2±28months (6-123months). Observed mortality rate was compared with that predicted by the MAGGIC Score. Patients were 61±12years old with EF 23±7%. Heart failure was due to ischemic (n=48, 59.3%) or idiopathic dilated (n=33, 40.7%) cardiomyopathy. EF increased from 23.1±7.9 to 29.4±8.6% (p<0.05), mean NT-proBNP decreased from 4395±3818 to 2762±3490ng/l (p<0.05) and mean peak VO2 increased from 13.9±3.3 to 14.6±3.5ml/kg/min (p=0.1). The overall clinical responder rate (at least 1 class improvement of NYHA within 6months or last follow-up) was 74.1%. 21 (25.9%) patients died during follow up, 11 (52.4%) due to cardiac conditions and 10 (47.6%) due to non-cardiac conditions. Mortality rates at 1 and 3years were 5.2% and 29.5% compared to mortality rates estimated from the MAGGIC risk score of 18.4% (p<0.001) and 40% (p=ns), respectively. Log-Rank analysis of all events through 3years of follow-up, however, was significantly less than predicted (p=0.022). CCM therapy improved quality of life, exercise capacity, NYHA class, EF and NT-proBNP levels during long-term follow up. Mortality rates appeared to be lower than estimated from the MAGGIC score.
Gesehen am 29.08.2017